The Correspondence Between Graphs and Alexandroff Spaces - Harbi, Badr Al (Communications in Mathematics and Applications, 2023)
In this paper, we study the correspondence between graphs and Alexandroff spaces. It is shown that a topological space \(X\) is Alexandroff if and only if \(X\) is a graph equipped with the \(X\)-right topology.
Keywords: Graph; Spectral; Prime spectrum; Ring; Alexandroff space